2014
DOI: 10.1590/s0100-204x2014000400009
|View full text |Cite
|
Sign up to set email alerts
|

Relações empíricas entre características dendrométricas da Caatinga brasileira e dados TM Landsat 5

Abstract: O objetivo deste trabalho foi ajustar modelos para estimar características dendrométricas da Caatinga brasileira a partir de dados do sensor TM do Landsat 5. Medidas de diâmetro e altura das árvores foram obtidas de 60 parcelas de inventário (400 m2), em dois municípios do Estado de Sergipe. A área basal e o volume de madeira foram estimados com uso de equação alométrica e de fator de forma (f = 0,9). As variáveis explicativas foram obtidas do sensor TM, após correção radiométrica e geométrica, tendo-se consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
2
6
0
6
Order By: Relevance
“…Thus, variations in the correlation values between vegetation indices and field variables can be a result of the spatial resolution of the images used or, according to Ponzoni (2001), the effect of the atmosphere and the soil must also be considered. Almeida et al (2014) used Landsat 5 TM images in the "Caatinga" area and verified that the variable basal area (m².ha -1 ) had no significant correlation with any variable derived from remote sensing. Reis et al (2018) used the vegetation indices MSAVI and NDVI to predict volume and observed a good correlation between these indices and the volume variable (NDVI = 0.49 and MSAVI = 0.45).…”
Section: Model Equationmentioning
confidence: 89%
“…Thus, variations in the correlation values between vegetation indices and field variables can be a result of the spatial resolution of the images used or, according to Ponzoni (2001), the effect of the atmosphere and the soil must also be considered. Almeida et al (2014) used Landsat 5 TM images in the "Caatinga" area and verified that the variable basal area (m².ha -1 ) had no significant correlation with any variable derived from remote sensing. Reis et al (2018) used the vegetation indices MSAVI and NDVI to predict volume and observed a good correlation between these indices and the volume variable (NDVI = 0.49 and MSAVI = 0.45).…”
Section: Model Equationmentioning
confidence: 89%
“…A possible alternative to integrate biomass estimates based on forest inventory measurements would be the use of satellite images or even LiDAR technology (Estornell et al 2011, 2012, Almeida et al 2014). Biomass models considering genus, families, successional groups, climatic variables and specific density of wood should be adjusted, tested at both local and regional levels, as well as on tropics scales with dry forest dominance.…”
Section: Discussionmentioning
confidence: 99%
“…O volume total sem casca das árvores foi obtido por meio de fator de forma 0,90 (Almeida et al, 2014), usualmente utilizado na região de estudo.…”
Section: Methodsunclassified